Dual PI3K/Akt Inhibitors Bearing Coumarin-Thiazolidine Pharmacophores as Potential Apoptosis Inducers in MCF-7 Cells - Rana M. Abdelnaby; Heba S. Rateb; Omaima Ali; Ahmed S. Saad; Rania I. Nadeem; Sahar M. Abou-Seri; Kamilia M. Amin; Nancy S. Younis; Rasha Abdelhady (MDPI AG, 2022)
Breast cancer is the most common malignancy worldwide; therefore, the development of new anticancer agents is essential for improved tumor control. By adopting the pharmacophore hybridization approach, two series of 7-hydroxyl-4-methylcoumarin hybridized with thiosemicarbazone (V-VI) and thiazolidin-4-one moieties (VII-VIII) were prepared. The in vitro anticancer activity was assessed against MCF-7 cells adopting the MTT assay. Nine compounds showed significant cytotoxicity. The most promising compound, VIIb, induced remarkable cytotoxicity (IC50 of 1.03 + 0.05 µM). Further investigations were conducted to explore its pro-apoptotic activity demonstrating S-phase cell cycle arrest. Apoptosis rates following VIIb treatment revealed a 5-fold and 100-fold increase in early and late apoptotic cells, correspondingly. Moreover, our results showed caspase-9 dependent apoptosis induction as manifested by an 8-fold increase in caspase-9 level following VIIb treatment. Mechanistically, VIIb was found to target the PI3K-α/Akt-1 axis, as evidenced by enzyme inhibition assay results reporting significant inhibition of examined enzymes. These findings were confirmed by Western blot results indicating the ability of VIIb to repress levels of Cyclin D1, p-PI3K, and p-Akt. Furthermore, docking studies showed that VIIb has a binding affinity with the PI3K binding site higher than the original ligands X6K. Our results suggest that VIIb has pharmacological potential as a promising anti-cancer compound by the inhibition of the PI3K/Akt axis.